Use of calixarenes bearing diazonium groups for the development of robust monolayers with unique tailored properties. Issue 19 (10th March 2020) - Troian-Gautier, Ludovic; Mattiuzzi, Alice; Reinaud, Olivia; Lagrost, Corinne; Jabin, Ivan
Abstract : Calixarene-based diazonium salts can be easily synthesized in a few steps. This review surveys recent examples that illustrate the key advantages of these highly reactive molecular platforms for surface modification. Abstract : Surface modification represents an active field of research that finds applications, amongst others, in the development of medical devices, sensors and biosensors, anti-biofouling materials, self-cleaning surfaces, surfaces with controlled wettability, corrosion resistance, heterogeneous catalysis and microelectronics. For some applications, surface functionalization with a nanometric-size monolayer is desired. In this review, efforts to covalently functionalize a wide array of surfaces with calixarenes bearing diazonium groups are described. More specifically, methodologies to obtain monolayers of calix[4 or 6]arene derivatives on conductive, semi-conductive or insulating surfaces as well as on nanoparticles are presented. The main advantages of this general surface modification strategy ( i.e. formation of true monolayers that can be post-functionalized, high robustness and control over the composition of the calixarene-based coating) and its current scope of applications and future challenges are discussed.